METHODS FOR COMPARISON OF FUTURISTIC MODELS (BASED ON THE POLISH FUTURISM) - Reha, Danylo (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
This article deals with the set of methods of comparative literature for conducting comparative studies between at least two national variants of futurism. In the article is proposed to use the term "futuristic model" for the tertium comparationis as a means of deciphering the content-intentional manifestations of manifestographic and poetic texts, as well as as a formative component of the futuristic worldview. The term "futuristic model" is new and introduced by us for the first time. The methods for comparing futuristic models can include, at least, the following methods: comparative-historical, genetic, contacts, typological, biographical, and methods of cultural-historical school. The methods listed above will make it possible to cover the entire spectrum of the development of national variants of futurism as widely as possible in order to compare them with each other (find common and distinctive features), and thus build a complete system of awareness of the existence of futurism in space and time.